Jack Russell terrier : bundle of energy - Lunis, Natalie (New York : Bearport, 2009)
Provides an introduction to Jack Russell terriers that discusses the breed's history, physical characteristics and behaviors and looks at Jack Russell terriers in popular culture.
Includes bibliographical references (p. 31) and index.
5.5
3-6
Keywords: Jack Russell terrier -- Juvenile literature; Dogs; Jack Russell terrier; Dogs; Jack Russell terriers